Diversity, Oppression, and Social Functioning: Person-in-Environment Assessment and Intervention - Appleby, George A.; Colon, Edgar; Hamilton, Julia (Pearson/Allyn and Bacon, 2011)
Keywords: Social work with minorities; Person-in-environment system; dept.swk; faculty_collection

From bumps in the road to the edge of chaos: The nature of change in adults - Keenan, Elizabeth King (Journal of Social Work, 2011)
This article explores the question of how human beings change, how change is constrained, and how change emerges out of and subsequently creates new forms of stability with adults. The emergence of Dynamic Systems Theories (DST) from developmental biology and neuroscience provide the tools to engage in such an understanding by attending to the issues of time, balance, influencing parameters (within person and sociocultural and material environments), and multiple adaptive and maladaptive pathways. DST provides the framework to understand the dynamic processes of bio-psychosocial factors that provide human beings with the stability and the flexibility to navigate the challenges and stressors of living. Complexity, the ability to experience inner continuity as one is changing, is a fluid balance that supports effective functioning. Findings: Key principles and concepts of DST describe multiple pathways of stability and change. A case example illustrates how DST helps social workers understand client experiences and responses to stressors, formulate initial and ongoing assessments, and monitor clients' participation in change activities. Application: Social workers seek to help people who experience an imbalance due to an inability to effectively respond to the negative impact of a stressor. By understanding the various pathways of balance and imbalance along the continuum of continuity to change, social workers can better understand how stressors are impacting specific clients, and subsequently the kinds of change that would best assist each client.
Keywords: change; complexity theory; dept.swk; dynamic systems theory; peer-reviewed; self-organization; stressors